Supporting Flexibility and Awareness in Localisation Workflows - DOHERTY, GAVIN; FEENEY, KEVIN CHEKOV; LEWIS, DAVID; LUZ, SATURNINO (My University, 2009)
A key strategy for supporting users in distributed work systems is to help them maintain awareness of the state of the work system and of the work being done by others. At the same time, many knowledge intensive industries are embracing the technologies that have underpinned the Web 2.0 movement to allow open user generation, annotation and modification of content. These technologies can potentially provide a useful platform for supporting awareness and distributed teamwork. However, as distributed content generating activities become more valuable, organisations aim to optimise them, often by modelling and monitoring the workflows involved and augmenting them with software services. Currently, however, these two approaches do not integrate well and there is little system support that integrates the centralised monitoring and management of workflow with the open communications that is characteristic of web-based user content generation. In this paper we examine the use of both techniques in the localisation industry, and based on this analysis we propose a platform that combines the visibility and awareness support of open content generation between users with their involvement in a centrally managed workflow.
PUBLISHED
Keywords: Localisation; Workflow